ANALISIS KUALITAS PELAYANAN REHABILITASI SESUAI STANDAR PELAYANAN BAGI PENYALAH GUNA NAPZA DI RUMAH DAMAI, GUNUNGPATI, SEMARANG - Risnawati Valentina; Anneke Suparwati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2017)
The prevalence of drug misuse to in Indonesia has reached 2.18% or about 4.022.702  people of the total population (aged 10-59 years). Semarang is a city that has a large number of residents and out of existing datareferred to the year 2019 the prevalence of drug users predicted 2.09% of the population, and potentially workers and students.  In accordance with the legislation of the Republic of Indonesia Number  35 in 2009 about Narcotics, the presence of massive rehabilitation movement of one hundred thousand to misusedrugs by 2015 will not be failed to find maximum results if done without a hardstruggle and high creativity. This research aims to analyze the quality of rehabilitation services according to the stipulations  the Ministry of social and the National Narcotics Agency. This research uses qualitative descriptive method with the subject of the research taken by using purposive  sampling. As for the researched is the standard human resources, institutional organizations (funding), infrastructure, and service of process. One of the drugs  rehabilitation in Semarang is Yayasan Rumah Damai  has been recognized by the Ministry of social and National Narcotics Agency. The main informant consists of Trustees, Chair, mentor, and the client of the Yayasan Rumah Damai. As for the informant triangulation is the staff of the National  Narcotics  Agency of the Rehabilitation  Deputy of the Central Java province and field Staff with disabilitiessocial welfare Social Service issues, youth, and sports city of Semarang. As for the results of this research are human resources, infrastructure, service of process the rehabilitation has not been run on the standard compliance services.